Respuesta :

Answer:

Option 2: [tex]f^{(-1)}(x) = -\frac{3}{4x}[/tex] is the correct answer.

Step-by-step explanation:

Given function is:

[tex]f(x) = -\frac{3}{4x}[/tex]

There are few steps to find inverse of a function. We will apply them one by one onto the function

Step 1: Replacing f(x) with y

[tex]y = -\frac{3}{4x}[/tex]

Step 2: Replacing y with x and x with y

[tex]x = -\frac{3}{4y}[/tex]

Step 3: Solving the equation in step 2 for y

[tex]x = -\frac{3}{4y}\\y = -\frac{3}{4x}[/tex]

Step 4: Replacing y with inverse of f

[tex]f^{(-1)}(x) = -\frac{3}{4x}[/tex]

Hence,

Option 2: [tex]f^{(-1)}(x) = -\frac{3}{4x}[/tex] is the correct answer.